Changes in excitability and GABAergic neuronal activity of the primary somatosensory cortex after motor learning - Pham, Manh Van; Saito, Kei; Miyaguchi, Shota; Watanabe, Hiraku; Ikarashi, Hitomi; Nagasaka, Kazuaki; Yokota, Hirotake; Kojima, Sho; Inukai, Yasuto; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Neuroscience, 2022)
Introduction It is widely known that motor learning changes the excitability of the primary motor cortex. More recently, it has been shown that the primary somatosensory cortex (S1) also plays an important role in motor learning, but the details have not been fully examined. Therefore, we investigated how motor skill training affects somatosensory evoked potential (SEP) in 30 neurologically healthy subjects. Methods SEP N20/P25_component and N20/P25 SEP paired-pulse depression (SEP-PPD) were assessed before and immediately after complex or simple visuomotor tasks. Results Motor learning was induced more efficiently by the complex visuomotor task than by the simple visuomotor task. Both the N20/P25 SEP amplitude and N20/P25 SEP-PPD increased significantly immediately after the complex visuomotor task, but not after the simple visuomotor task. Furthermore, the altered N20/P25 SEP amplitude was associated with an increase in motor learning efficiency. Conclusion These results suggest that motor learning modulated primary somatosensory cortex excitability.